Jailing Immigrant Detainees: A National Study of County Participation in Immigration Detention, 1983–2013. Issue 1 (29th January 2020) - Ryo, Emily; Peacock, Ian
Abstract : Hundreds of county jails detain immigrants facing removal proceedings, a civil process. In exchange, local jails receive per diem payments from Immigration and Customs Enforcement. Immigration detention thus presents a striking case of commodification of penal institutions for civil confinement purposes. Yet we know very little about the counties participating in this arrangement and the predictors of their participation over time. Our study offers the first systematic analysis of immigration detention in county jails using new and comprehensive panel data on jails across the United States. First, we find that the number of counties confining immigrant detainees steadily increased between 1983 and 2013, with the largest growth concentrated in small‐ to medium‐sized, rural, and Republican counties located in the South. Second, our regression analyses point to a number of significant predictors of county participation in immigration detention: (a) worsening labor market conditions, combined with growing excess bed space for the criminal inmate population; (b) an increasing Latino population up to a certain threshold level; and (c) increasing Republican Party strength. These findings have important implications for current debates raging across the United States about the proper role of local communities in detaining immigrants.